2012
DOI: 10.9738/cc150.1
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Patients With Gastric Cancer Who Underwent Proximal Gastrectomy

Abstract: Proximal gastrectomy (PG) has been introduced for patients who are preoperatively diagnosed with early gastric cancer located in the upper third of the stomach. In the present study, we compared the prognosis of patients who underwent PG with that of patients who underwent total gastrectomy (TG). Between 1997 and 2006, 51 patients were diagnosed with early gastric cancer located in the upper third of the stomach and underwent PG. In the same period, 35 patients were diagnosed with early gastric cancer and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
(12 reference statements)
0
14
1
1
Order By: Relevance
“…While there is still lack of agreement that PG-JI or PG-DT can replace TG-RY, PG-JI and PG-DT, as function-preserving surgery, do have several advantages over TG-RY [3,[6][7][8][12][13][14][15][16][17]. First, the remnant stomach offers significantly increased food intake volume and better QOL for patients.…”
Section: Discussionmentioning
confidence: 99%
“…While there is still lack of agreement that PG-JI or PG-DT can replace TG-RY, PG-JI and PG-DT, as function-preserving surgery, do have several advantages over TG-RY [3,[6][7][8][12][13][14][15][16][17]. First, the remnant stomach offers significantly increased food intake volume and better QOL for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 3921 individuals comprising the base population, 204 of 300 patients with T1 upper-third gastric cancer underwent proximal gastrectomy. Although LNs lying along the right gastric and right gastroepiploic vessels are not dissected, survival outcome after proximal gastrectomy performed for early upper-third gastric cancer is known to be comparable with that after total gastrectomy [17,18]. Several reports have demonstrated that the occurrence of metastasis from upper-third gastric cancer to LNs at the no.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported inconsistent results about relationship between age and prognosis [4][5], which may result from the absence of unified criterion of age groups. The elderly are identified as old people who are more than 65 years old by World Health Organization (WHO).…”
Section: Discussionmentioning
confidence: 99%